Postmastectomy radiation therapy in early breast cancer: Utility or futility?. (March 2020) - Montero, Angel; Ciérvide, Raquel; García-Aranda, Mariola; Rubio, Carmen
Graphical abstract: Highlights: pTis: Large tumor size, age <40, margins close (<1 mm)/positive. pT1-2 N0: Presence of at least 2 risk factors: age <50 or premenopausal status, tumor size ≥2 cm, presence of LVI, high grade, positive, close margins, lack of systemic treatment, unfavorable subtype (HER2+/TN). pN1mi/N0(i+): Presence of axillary node micrometastases or at least 2 previously described risk factors. Abstract: Postmastectomy radiation therapy (PMRT) has been shown to reduce the risk of locoregional recurrence (LRR), in patients with locally advanced breast cancer who are considered of high-risk because of large tumors (>5 cm) or presence of axillary lymph-node involvement, as well as to reduce breast cancer mortality. However, controversy still remains with respect to indication of PMRT in case of early-stages invasive tumors. This review aims to analyze the impact that PMRT has on final results in women with breast tumors in different scenarios that would otherwise be considered as early breast cancer, such as extensive DCIS, tumors without axillary lymph-node involvement or with minimal microscopic nodal-involvement. The existence of risk factors including young age, premenopausal status, and presence of lymphovascular invasion (LVI), high grade or tumor size >2 cm has been associated with an increased risk of LRR in these patients at early-stages and advises to consider PMRT in selected cases.